The Effects of Religious Activities on Fostering Positive Behavior in Junior High School - Idris, Muhammad; Asha, Lukman; Yuniyanti, Indah; Islahuddin, Islahuddin (International Journal of Islamic Teaching and Learning, 2024)
Learner behavior can be nurtured through both academic and non-academic activities at school. Educational activities may take the form of curricular, co-curricular, and extracurricular programs. Religious activities in schools represent academic efforts through co-curricular and extracurricular channels. As educational institutions, schools must be capable of cultivating a generation that exhibits positive behavior, in alignment with the broader goal of fostering students with noble character. This study aims to explore the impact of extracurricular or non-academic activities on students' positive behavior. A qualitative case study approach was employed, with data collected through direct observation of extracurricular activities conducted by the school. The data were analyzed using Milles and Huberman's interactive technique. The findings indicate that religious extracurricular activities are well-structured and align with the intended objectives, taking place regularly on Fridays. These activities include Quran recitations, religious sermons, the chanting of shalawat, prayers for community welfare, and student participation in Islamic holiday commemorations to enhance their love for religion. Furthermore, five key positive behavioral outcomes were identified: i) responsibility, ii) tolerance, iii) cooperation, iv) creativity, and v) religiosity. The successful implementation of religious activities in Indonesian secondary schools offers a valuable model for other educational institutions aiming to foster positive student behavior